Pengelolaan Zakat, Infak, dan Sedekah dalam Pengembangan Usaha Mikro di Unit Pengelola Zakat (UPZ) Kecamatan Tajurhalang - Zinedine Zidan; Ibdalsyah Ibdalsyah; Hambari Hambari (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This research addresses the issue of how ZIS funds are managed at the UPZ of Tajurhalang District in the development of micro enterprises, as well as the effectiveness of UPZ programs in assisting micro entrepreneurs. The purpose of this study is to understand the management of ZIS funds for developing micro enterprises in Tajurhalang District and to explore the efforts and implementation of productive business capital programs at UPZ. The research uses a qualitative method with a descriptive approach, which describes the issues occurring in the field. Data collection techniques include observation, interviews, and documentation. The results of the study show that effective management is essential for successful fundraising activities, as gathering and managing funds is not easy and involves various processes and dynamics. There must be a management process in fundraising, including planning, organizing, executing, and monitoring. ZIS funds, which were initially managed in non-productive sectors, can now be redirected to productive sectors.